2009
DOI: 10.1523/jneurosci.4362-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Drives Endocannabinoid-Mediated Disinhibition in a Midbrain Descending Analgesic Pathway

Abstract: Substance P is thought to play an essential role in several forms of supraspinally mediated analgesia. The actions of substance P on synaptic transmission within descending analgesic pathways, however, are largely unknown. Here, we used whole-cell recordings from rat midbrain slices to examine the effects of substance P on GABAergic and glutamatergic transmission within the periaqueductal gray (PAG), a key component of a descending analgesic pathway that projects via the rostral ventromedial medulla (RVM) to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 59 publications
3
67
0
Order By: Relevance
“…The lack of effect of cholecystokinin on TTX-resistant miniature IPSCs suggests that the cholecystokinin-induced reduction in presynaptic GABA release involved additional mechanisms external to the synapse, rather than direct postsynaptic CCK1 receptorinduced retrograde endocannabinoid signaling, as observed for mGluR5 and M1 mAChR receptor signaling in PAG (Drew et al, 2008;Lau and Vaughan, 2008). We have previously shown that activation of G q -coupled NK1 and NTS1/2 receptors indirectly activates the mGluR5-endocannabinoid system by enhancing endogenous glutamate release (Drew et al, 2009;Mitchell et al, 2009). In this study, CCK-S produced neuronal depolarization and an increase in spontaneous action potential-dependent glutamatergic EPSCs, however, we cannot rule out a direct CCK receptor-mediated enhancement of presynaptic glutamate release (Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The lack of effect of cholecystokinin on TTX-resistant miniature IPSCs suggests that the cholecystokinin-induced reduction in presynaptic GABA release involved additional mechanisms external to the synapse, rather than direct postsynaptic CCK1 receptorinduced retrograde endocannabinoid signaling, as observed for mGluR5 and M1 mAChR receptor signaling in PAG (Drew et al, 2008;Lau and Vaughan, 2008). We have previously shown that activation of G q -coupled NK1 and NTS1/2 receptors indirectly activates the mGluR5-endocannabinoid system by enhancing endogenous glutamate release (Drew et al, 2009;Mitchell et al, 2009). In this study, CCK-S produced neuronal depolarization and an increase in spontaneous action potential-dependent glutamatergic EPSCs, however, we cannot rule out a direct CCK receptor-mediated enhancement of presynaptic glutamate release (Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the cholecystokinin-induced inhibition of evoked IPSCs is also mediated by the endocannabinoid system, because it was abolished by the cannabinoid CB1 antagonist/inverse agonist AM251. Furthermore, the endocannabinoid involved in this process was likely to be 2-arachidonyl glycerol because the CCK-Sinduced inhibition was blocked by an inhibitor of DAGLa, the enzyme which mediates its production via Gq-coupled GPCRs in a number of brain regions, including the PAG (Bisogno et al, 2003;Drew et al, 2009;Jung et al, 2005;Lau and Vaughan, 2008;Uchigashima et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations